2002
DOI: 10.1002/bip.10296
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and biology of the ramoplanin family of peptide antibiotics

Abstract: The peptide antibiotic ramoplanin factor A2 is a promising clinical candidate for treatment of Gram-positive bacterial infections that are resistant to antibiotics such as glycopeptides, macrolides, and penicillins. Since its discovery in 1984, no clinical or laboratory-generated resistance to this antibiotic has been reported. The mechanism of action of ramoplanin involves sequestration of peptidoglycan biosynthesis Lipid intermediates, thus physically occluding these substrates from proper utilization by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
81
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(85 citation statements)
references
References 74 publications
4
81
0
Order By: Relevance
“…The structure provides a high-resolution view of the ramoplanin dimer and illustrates a potential means by which ramoplanin interacts with bacterial target membranes. Together with recent structure-activity studies, it also suggests a mechanism by which ramoplanin recognizes its Lipid II ligand (10,12,15,(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…The structure provides a high-resolution view of the ramoplanin dimer and illustrates a potential means by which ramoplanin interacts with bacterial target membranes. Together with recent structure-activity studies, it also suggests a mechanism by which ramoplanin recognizes its Lipid II ligand (10,12,15,(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 61%
“…At least three forms are known, A1, A2, and A3; these forms differ in their acyl chain substituents, but possess essentially identical antibiotic activities. Ramoplanins are structurally and functionally related to ramoplanose, which is produced by Actinoplanes strain U.K.-71,903 and which differs from factor A2 by one mannose unit (7), and to enduracidin A and B, which are produced by Streptomyces fungicidicus B5477 (8)(9)(10). This paper focuses on the ramoplanin A2 isomer, the most abundant among the A1-A3 forms; for simplicity's sake, we refer to this isomer as ramoplanin for the remainder of the manuscript.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CDA variants which contain either (2R,3S)-3-hydroxyasparagine (3-OHAsn) or (2R,3S)-3-phosphohydroxyasparagine (3-OPAsn) at position 9 are also known. Whilst 3-OHAsn is common to a number of peptide antibiotics, including A54145 (Fukuda et al, 1990;Miao et al, 2006), katanosin B (Kato et al, 1988) and ramoplanin (Walker et al, 2005;McCafferty et al, 2002), 3-phosphohydroxyasparagine has not been found elsewhere in nature, to date.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed the subsequent processing of the amino acid b-hydroxyl groups by further oxidation (Chen et al, 2002), glycosylation (Lu et al, 2004), macrolactonization (Kato et al, 1988;Walker et al, 2005;McCafferty et al, 2002), methylation (Miao et al, 2006) or in the case of CDA, phosphorylation, serves to increase the structural diversity of nonribosomal peptides and related products, resulting in a wide range of biological activities. Of the many bhydroxylated amino acids and derivatives found in nonribosomal peptides, some arise as a result of the oxidation of free amino acids prior to peptide assembly (Yin & Zabriskie, 2004;Ju et al, 2004;Haltli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%